An Analysis of Comparative Lexical Cohesion Between BBC News and Jakarta Post News - Agustian, Agustian; Arsyad, Safnil (UNIB Press, 2023)
Abstract Research conducted by researchers was related to Lexical Cohesion (repetition, synonym, superordinate, general word, and collocation). The purposes of this research were (1) to find out the comparison of lexical cohesion between BBC News and The Jakarta Post News; (2) to find out the type of lexical cohesion between BBC News and Jakarta Post; and (3) to find out the dominant use of lexical cohesion in BBC News and The Jakarta Post News. Descriptive qualitative was used in this study, while the source of the data was taken from news texts written by BBC News and The Jakarta Post News, totaling 20 news about the Qatar 2022 world cup football, consisting of 10 news texts from BBC News and 10 news texts from The Jakarta Post. To analyze the data, the researchers used the Halliday and Hassan’s theory. The results found that for Lexical Cohesion for BBC News, there were 214 repetitions, 0 synonyms, 0 superordinate, 2 general words, and 33 collocations. So, the total Lexical Cohesion is 249. While for The Jakarta Post News, it was found 429 repetitions, 9 synonyms, 0 superordinate, 20 general words, and 25 collocations. So, the total of lexical cohesions found is 483. From the comparison of the data above, The Jakarta Post News has more types of Lexical Cohesion namely 483, compared to BBC News which only found 249 types of Lexical Cohesion. The dominant type of Lexical Cohesion in this research is the type of repetition.